STEM-Problem Based Learning: Pembelajaran Inovatif untuk Meningkatkan Literasi Sains Siswa di Era Industri 4.0 - Suyidno, Suyidno; Fitriyani, Fitriyani; Miriam, S; Mahtari, S; Siswanto, Joko (Universitas PGRI Semarang, 2022)
In the industrial era 4.0; STEM literacy plays an important role in the innovation of science and technology products, but this literacy is not trained in schools. Therefore, this article will analyze the feasibility of STEM-Problem-Based Learning (STEM-PBL) in improving students' scientific literacy. This study uses the ADDIE development model and trials were conducted on 23 students of class X SMA in Banjarmasin. Collecting data using the instrument of observing the learning implementation, response questionnaires, and scientific literacy tests. The results showed that students were able to carry out STEM-PBL activities well at each meeting and gave a positive response to these activities. In addition, the increase in scientific literacy in most students is in the high (26%) and moderate (61%). Although 13% of students in the low criteria, overall have experienced an increase in scientific literacy. So, STEM-PBL is feasible to improve students' scientific literacy in the industrial era 4.0Keywords: problem based learning, scientific literacy, STEM